Answer :
Answer: x = -3
Step-by-step explanation:
12x - 9 = 10x - 15
Add 9 to each side
12x = 10x - 6
Subtract 10x from each side
2x = -6
Divide by 2
x = -3
Answer:x=-3
Step-by-step explanation:
first you want to have the variables in one side so subtract the 10x from both sides. and it will give you .
12x-9=10x-15 to 2x-9=-15
Now you want to leave the nine to other side in order to make the equation legible. 2x=-6
. Finally you divide both sides by 2 in order to have x by itself.
2x/2=-6/2
the two cancels out and its left with x=-3